HUBUNGAN KARAKTERISTIK SOSIAL EKONOMI PETANI PADI SAWAH DENGAN KEI-KUTSERTAAN DALAM PENYULUHAN PERTANIAN DI DESA KAMANGA KECAMATAN TOMPASO KABUPATEN MINAHASA - Welson Marthen Wangke (Sam Ratulangi University, 2012)
This study aims to analyze the relationship between socio-economic characteristics rice farmers in participat-ing in agricultural extension in the Village District of Tompaso Kamanga.The method used in this research is quantitative method. The research was conducted in the Village District of Tompaso Kamanga Minahasa regency. The number of respondents were 30 farmers: Simple Random Sam-pling. By using questionnaires. The variables measured were: age is measured in (year), education is formal education (elementary Graduate, Graduate from junior high school, go to college, PT), revenue is measured from the income of the paddy rice farming (USD), the status of land ownership (see from their own land and tenants and or penyakap), participation in agricultural extension (seen from the frequency of attendance). To determine the socio-economic factors that influence the selection of a variety of extension methods used Spearman Rank correlation formula (Siegel, 1997). The results showed that the characteristics of the mem-bers of the real touch with the level of participation and vice versa if the value of the probability (P)> Î±, mean that there is no real relationship between the characteristics of the members of the participation rate.Keywords: Relationship, Characteristics, Farmers, Agricultural Extension